(untitled) (Intelligere, 2015)
The paper starts out by presenting the approach to the history of science based on causal models, discussing the postulation of counterfactual histories of science. Three different types of counterfactual analyses may be done in the historical sciences, all of which have the benefit of hindsight. Economic history and history of technology are characterized by their reasonable predictability; history of science and mathematics by their objectivity; and the third class, which includes “virtual history” and biological evolution, because of its vast scope of future possibilities.